Immune Response to Protein Corona: Unfolded Protein Corona Surrounding Nanotubes Influence the Innate and Adaptive Immune System (Adv. Sci. 8/2021). Issue 8 (22nd April 2021) - Park, Jun‐Young; Park, Sung Jean; Park, Jun Young; Kim, Sang‐Hyun; Kwon, Song; Jung, YunJae; Khang, Dongwoo
Abstract : In article number 2004979, Dongwoo Khang, YunJae Jung, and co‐workers investigate the innate and adaptive immune response triggered by protein corona surrounding nanotubes. It was confirmed that conformational changes of protein structures driven by conjugation of nanotubes elicit immune activation of neutrophil and natural killer cells. The elevation of these innate immune cells subsequently induces the activation of T cells. This suggested mechanism can provide a platform technology for activating the innate immune cells that could be readily adapted to immunotherapies in the near future.